Relationship Between Traveling Habits and Happiness Index - Novi Handayani; Iqlima Zalfa Syahrani (International Journal of Travel, Hospitality and Events, 2025)
Purpose: This study aims to determine the correlation between travel habits and the happiness index. Many people have recently experienced stress at work and even among students. The ongoing trend is to travel, which could reduce stress levels and increase happiness. Research methods: This quantitative study uses statistical data analysis with the Normal P-P Plot test and Pearson Correlation test. Data collection techniques used questionnaires with 100 Gen Z and millennial respondents. Results and discussion: The analysis shows a significant relationship between traveling habits (variable X) and the happiness index (variable Y), with high reliability and correlation values. Implication: These findings support the hypothesis that traveling habits strongly influence an individual's happiness level, which aligns with previous research showing that traveling can improve mental and physical well-being.